Educational Intervention on the Knowledge of Monkeypox Virus among Undergraduate Students in Rawalpindi; a Single Institution Quasi-Experimental Study - Hina Shan; Maryam Shan; Huzaifa Akram; Uzma Hassan; Raima Asif; Shazia Naqvi (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: The multi-country outbreak of Monkeypox (Mpox) in several regions has threatened the world, which is still confronted by the COVID-19 pandemic. To assess the effect of educational intervention on knowledge of epidemiology, prevention, and control of Monkeypox in undergraduate students.